AAPM Task Group Report 272: Comprehensive acceptance testing and evaluation of fluoroscopy imaging systems. Issue 4 (27th January 2022) - Lin, Pei‐Jan Paul; Goode, Allen R.; Corwin, Frank D.; Fisher, Ryan F.; Balter, Stephen; Wunderle, Kevin A.; Schueler, Beth A.; Kim, Don‐Soo; Zhang, Jie; Zhou, Yifang (Jimmy); Jenkins, Peter A.; Mahmood, Usman; et al.
Abstract: Modern fluoroscopes used for image guidance have become quite complex. Adding to this complexity are the many regulatory and accreditation requirements that must be fulfilled during acceptance testing of a new unit. Further, some of these acceptance tests have pass/fail criteria, whereas others do not, making acceptance testing a subjective and time‐consuming task. The AAPM Task Group 272 Report spells out the details of tests that are required and gives visibility to some of the tests that while not yet required are recommended as good practice. The organization of the report begins with the most complicated fluoroscopes used in interventional radiology or cardiology and continues with general fluoroscopy and mobile C‐arms. Finally, the appendices of the report provide useful information, an example report form and topics that needed their own section due to the level of detail.